2011
DOI: 10.1038/eye.2011.220
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot randomised controlled trial of face-down posturing following phacovitrectomy for macular hole

Abstract: Background To gather information on the effect of postoperative face-down posturing following combined phacoemulsification and vitrectomy for macular hole surgery in order to assist in the design of a larger definitive study. Methods Thirty phakic patients with stage II-IV full-thickness macular hole had combined phacoemulsification and pars plana vitrectomy with internal limiting membrane peel and 14% perfluoropropane (C 3 F 8 ) gas. At the conclusion of surgery, patients were randomised either to face-down p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…11 The visual acuity outcomes in this study are less good than those in our companion study. 18 This difference may reflect the effect of lens opacities in subjects in this study and the earlier assessment of outcome (6 weeks vs 6 months).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…11 The visual acuity outcomes in this study are less good than those in our companion study. 18 This difference may reflect the effect of lens opacities in subjects in this study and the earlier assessment of outcome (6 weeks vs 6 months).…”
Section: Discussionmentioning
confidence: 81%
“…Simultaneous cataract surgery may facilitate a more complete vitrectomy enabling injection of a larger volume of gas than in phakic eyes, which could reduce the need for face-down positioning in this group of subjects. This has been investigated in a companion study 18 that suggests no benefit from posturing when vitrectomy is combined with cataract surgery. Furthermore, Guillaubey et al arbitrarily used a range of tamponade gases according to the size of the macular hole and acknowledged that this could also be a source of potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…The need for posturing is debated with many studies showing successful non-posturing surgery in holes <400 μm and often with the use of short-acting gases [5,15,16,17,18]. Large holes are still usually treated with longer-acting gases and posturing [5,6,7,19,20] although the requirement for posturing is debated and a further study is needed [21]. For about 3/4 (72%) of our patients' vitrectomy surgery would currently be the only available treatment option but in only approximately a 1/3 of the cases (28.5%), would vitrectomy, ILM peeling, long-acting gas and post-operative face-down posturing be recommended by the majority of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12,[24][25][26][27][28] The results of recent comparative studies 12,[26][27][28] suggested no statistically significant difference in the closure rates between no posturing or short-term posturing and standard posturing. However, there was a tendency for the closure rate to be better with standard posturing than with no or short-term posturing, for example, posturing versus no posturing was 97.4% versus 87.5% in a study by Guillaubey et al 26 27 Nonetheless, these results must be questioned because 800 cases are theoretically required to achieve a 95% confidence interval.…”
Section: Discussionmentioning
confidence: 95%